The achievements of the European Monetary System - Artis, Michael J.; Taylor, Mark P. (Economic & Social Studies, 1989)
This paper attempts to provide some answers to a number of related questions: Has the EMS reduced (real or nominal, bilateral or effective) exchange rate volatility? If so, has this been at the expense of increased interest rate volatility? How important have capital controls been for the operation of the EMS? Has the exchange rate mechanism reduced the volatility of unanticipated exchange rate changes? Has the EMS been effective in making Exchange Rate Mechanism (ERM) currencies close substitutes? What have been the implications of the EMS for the longer-run stabilisation of real exchange rates? Because of the uncertainty surrounding the statistical distributions of changes in asset prices in general and exchange rates in particular, an innovative theme of the paper is the use of non-parametric or semi-non-parametric econometric and statistical procedures wherever possible. Briefly, we conclude that the EMS has reduced the volatility of both exchange rates and interest rates', that capital controls probably have been important in its operation and that it has reduced the conditional volatility of exchange rates. We attribute many of these findings to the enhanced credibility of the exchange rate policies of ERM member countries. Some of our findings, however, namely that ERM member currencies do not appear to be perfect substitutes and that there is evidence of long-run misalignment within the EMS, do indicate that the EMS may indeed still be in its early days in terms of some of its longer-term goals.
Keywords: European economics; European Monetary System; EMS